Repercussões da intervenção fonoaudiológica em falantes de uma segunda língua. - Cananéa, Ingrid Chaves (2010)
The aim of this study is to compare the pronunciation of consonants in American English among a group of speakers of this language as a foreign language before and after speech therapy. It outlined a phonetic profile of students of American English as a foreign language noting difficulties on consonants pronunciation. For this analysis, changes on consonant production after speech therapy were observed, comparing the initial with final pronunciation performance. It was used the acoustic analysis to obtain objective results. This discussion suggests the inclusion of speech therapy as a strategy for teaching pronunciation in English. In this study, it was selected 6 students of American English as second language for at least 1 year and maximum 3 years and had started this study after 18 years old, 2 males and 4 females. The recordings were performed in quiet environment. To perform the acoustic analysis it was used the computer programs Audacity, version 1.3 beta and Praat, version 5.0.47. The results were discussed and substantiated in the acoustic theory of speech production and the use of speech therapy. The results pointed out the possibility of change in the pattern of articulatory phonemes chosen for adult learners of American English as a foreign language. There were satisfactory articulatory changes in 100% of students with difficulty on voiced and unvoiced affricative alveolar and on palatal liquid voiced, 83.3% of students with difficulty on unvoiced fricative dental and 66.6% of students with difficulty on voiced dental fricative. From this study, it is expected to contribute to the expansion of the field of study and work of the Speech Therapists as to improve student's pronunciation of a foreign language through the speech therapy.